Yorick and Bönes - Tankard, Jeremy; Tankard, Hermione (Harper Alley, 2020)
Yorick is a skeleton who is brought to life after a collision between a hot dog vendor and a witch and later dug up by a dog named Bones. The two begin an unlikely partnership and go on an adventure to find other people to be friends with in the modern world. They soon learn that friendship is closer than they think.